Zotero Sebagai Alat Bantu Manajemen Referensi Bagi Mahasiswa Dalam Menyusun Tugas Ilmiah - Ossa Sunnah (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Effective reference management is an important component in academic writing, especially for students writing scientific assignments. Zotero is a reference management software that offers a variety of features to help students organize, store, and cite their reference sources efficiently. This article discusses the role and benefits of Zotero as a reference management tool, including its ability to integrate with various databases and browsers, ease of managing various types of sources, and collaborative features that support group work. Through the use of Zotero, students can improve the quality of their writing by ensuring accuracy and consistency in reference management. The study also includes a literature review on the effectiveness of Zotero and a survey of the use of this software among college students.